Berkembang dalam Tekanan: Pesantren Sidoresmo dan Resistensinya Menghadapi Pemerintah Hindia Belanda di Surabaya Akhir Abad XIX – Awal Abad XX - wahyudi, johan; Wahyudhi, Johan (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
This study explores the social and political life of the Sidoresmo Islamic boarding school (pesantren) from the late 19th century to the early 20th century. The research focuses on the socio-economic dynamics of the surrounding community, the relationship between the pesantren and the local Muslim society, as well as the pesantren's involvement in anti-colonial resistance against the Dutch East Indies government. The study employs a historical approach, relying primarily on official colonial government reports and period newspapers as primary sources. These written records are complemented by oral accounts transmitted across generations, particularly from fathers or grandfathers to current local informants. The research reveals several important findings concerning the strategic role of the pesantren in shaping communal life and local resistance. One of the key discoveries is that communal life in Sidoresmo was not only religiously structured but also served as a social foundation for resistance movements. Furthermore, the study sheds light on the 19th-century pesantren education model, which exhibits distinctive characteristics, such as the kiai-santri relationship, traditional methods of Islamic book (kitab kuning) instruction, and the integration of religious education with cultural resilience. These aspects of pesantren education in the 19th century remain underexplored in modern Indonesian historiography. Thus, this study contributes to a broader understanding of the pesantren not merely as a religious institution, but as a dynamic socio-political and educational force in pre-independence Indonesian history. It aims to enrich the discourse on pesantren-based resistance and local Islamic education during colonial times.